Development of STEM Based Mathematics Learning Instruments to Improve Students’ Critical Thinking Skills in PBL Model (Unnes Journal of Mathematics Education, 2022)
The research aim was to develop STEM-based learning instruments to improve students' critical thinking skills used in the PBL model that was valid, practical, and readable by students. The research used a simplified 4-D development model in the research and development research method, which consisted of three stages; define, design, and develop. It was because of the Covid-19 pandemic that the learning process was held online, and the effectiveness testing or dissemination stage couldn’t be held. The learning instruments consisted of a syllabus, lesson plan, learning material, and student worksheet. Learning instruments’ validation testing stated that the learning instruments were valid with the average scores for syllabus was 3.82 out of 4.00, for lesson plan was 3.79 out of 4.00, for learning material was 3.85 out of 4.00, and for student’ worksheet was 3.80 out of 4.00. Learning instruments’ practicality testing stated that the learning instruments were practical to be used during the learning process, with scores of it were 97.50% for syllabus, 96.43% for the lesson plan, 95.83% for learning material, and 93.06% for student worksheets. Learning instruments’ readability testing stated that the learning instruments were readable by students, with scores of it were 82.78% for learning material and 80.83% for students’ worksheets.